The effect of fluorination of aramid fibers on vinyl ester composites. Issue 5 (17th October 2018) - Wirti, Marilu; Biondo, Gabriel Roman Ros; Romanzini, Daiane; Amico, Sandro C.; Zattera, Ademir J.
Abstract : Composite materials are associated with low densities and high mechanical performance, thus favoring protection of personnel, military vehicles and aircrafts. Polyaramid fibers like Kevlar®, are well‐known for their ballistic performance, but their chemically inert and smooth surface hinders interaction with polymeric resins. The objective of this work is to surface treat aramid fibers with fluoride to improve fiber reactivity and interfacial adhesion with a thermoset matrix. The Kevlar®/vinyl ester composites were prepared by compression molding and characterized. Composites with treated fibers had lower void content and higher glass transition temperature, stiffness, storage and loss module. Nevertheless, they showed lower tensile strength, impact strength, damping, and adhesion factors. The treated fiber composites also presented higher adhesion between fibers and matrix, resulting in less chain segment movement and higher energy dissipation. POLYM. COMPOS., 2018. © 2018 Society of Plastics Engineers